The role of hydrogeological setting in two Canadian peatlands investigated through 2D steady-state groundwater flow modelling. Issue 15 (18th November 2017) - Quillet, Anne; Larocque, Marie; Pellerin, Stéphanie; Cloutier, Vincent; Ferlatte, Miryane; Paniconi, Claudio; Bourgault, Marc-André
ABSTRACT: This study investigated how hydrogeological setting influences aquifer–peatland connections in slope and basin peatlands. Steady-state groundwater flow was simulated using Modflow on 2D transects for an esker slope peatland and for a basin peatland in southern Quebec (Canada). Simulations investigated how hydraulic heads and groundwater flow exported toward runoff from the peatland can be influenced by recharge, hydraulic properties, and heterogeneity. The slope peatland model was strongly dominated by horizontal flow from the esker. This suggests that slope peatlands are dependent on the hydrogeological conditions of the adjacent aquifer reservoir, but are resilient to hydrological changes. The basin peatland produced groundwater outflow to the surface aquifer. Lateral and vertical peat heterogeneity due to peat decomposition or compaction were identified as having a significant influence on fluxes. These results suggest that basin peatlands are more dependent on recharge conditions, and could be more susceptible to land use and climate changes.